MEASURING CUSTOMER GAP IN GEROBAK BETAWI TAMAN RATU, JAKARTA BARAT - Wiranata, David Anugrah; Suharto, Yulianto (Journal of Business and Management, 2018)
Abstract. Gerobak Betawi Taman Ratu as one of the 4 branches of Gerobak Betawi restaurant. Is a restaurant that specialized in serving Indonesia ethnic food. With the increasing number of restaurants that specialized in the same type of food, Gerobak Betawi feels they need to have an advantage that will make them stand out from their competitor. This research use SERVQUAL method for measuring the service quality of Gerobak Betawi Taman Ratu. It is presented in the questionnaire survey which is a qualitative method. The paper will be focusing on service quality and customer gap. Based on the study, it shows that not all of the dimensions are negative. Two out of five dimensions got positive gap. Gerobak Betawi need to improve their service quality by prioritizing the dimension with the negative gap. And the service quality is still in the zone of tolerance of their customer. From the result of the study there are some recommendation that could be made. The recommendation will be some things that they could do differently or new thing they need to implement in their restaurant. This study will help them to know better their current service quality from the perspective of their customer.Keywords: customer gap, restaurant, service quality, SERVQUAL, zone of tolerance